Alison Light -- Inside history : from popular fiction to life-writing - Light, Alison, 1955- (The feminist library, 2022)
A collection of thought-provoking essays spanning thirty-five years of Alison Light's workProvides a historicising collection of essays, by a major critic, exemplifying and opening up feminist cultural politics to new readersOffers a way into a variety of texts and genres - including popular fiction, drama, film - as well as single authors, united by a lively and readable feminist approachExtends current thinking on national identity and Englishness from a writer who helped open these fieldsSpeaks to the new and growing academic interest in 'life-writing'Includes shorter pieces which also encapsulate complex arguments as well as examples of original life-writing by the authorIncludes an autobiographical introduction which contextualises and historicises the author's work and reflects on itAlison Light - Inside History addresses a number of the central preoccupations within feminist cultural criticism over this period: the nature of writing by women and what women writers might or might not share; the place of such writing in any literary history or cultural analysis; the politics of popular culture and the question of pleasure; women's relation to ideas of national identity and other forms of belonging; and finally, their contribution to life-writing in its different genres. The volume offers a lively, wide-ranging way into feminist debates, touching on a number of major authors from Alice Walker to Virginia Woolf, on genre fiction, and on the writing of memoir and biography. Chronologically arranged, the essays and short 'think-pieces' chart Alison Light's own intellectual formation as a critic and writer within a wider collective politics. This is explored and contextualised in an autobiographical introduction.